PARTICIPAÇÃO E DEMOCRACIA NA GESTÃO DE RECURSOS HÍDRICOS: ESTUDO SOBRE OS EFEITOS DA ATIVIDADE DE GERAÇÃO HIDRELÉTRICA NA BACIA HIDROGRÁFICA DO LITORAL PARANAENSE - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2010)
Is there a democratic management of the water resources at the coastline basin of Paraná? Does the hydroelectric generation activity influence this fact? The answer of these questions constitute the master line in the conduction of this academic work, that has as interest period the one before the Water Resources Federal Law (Federal Law nº 9433/1997) up to the present date. The implementation verification (or not) of the democratic management and participative of the water at the studied place was searched through deepen at the researched place and it´s social relations, search of specific knowledge about the hydroelectric generation activity effects, analyses of the referential juridical limit of the hydroelectric generation activity and a theory conceptual incursion. The specific objective of the work addresses to determinate the existence of water participatory management in the water parting of the Paraná coast, the influence of hydroelectric dams in this context, but also the generation of economic externalities and negative environmental impacts associated with the operation of these developments in the region. The advance in the process of research and preparation of the dissertation came from a perspective rooted in the complexity of the relationships between society and environment, establishing a starting question that was deployed in hypotheses, which gave rise to variables, whose determination supported the answer to the proposed problem. Regarding the database, information was collected with the government, market players, researchers, civil society and coastal communities, combining those produced in an environment of scientific knowledge with information marked by common sense impressions. The link of the theory study and of the collected data will allow the initial question to be answered, which signalizes to the non implementation of the democratic management and participative of the water resources at the coastline basin of Paraná, with influence of the hydroelectric generation activity for the perpetuation of this condition.
Keywords: democracia; participação, gestão de recursos hídricos; bacia litorânea do Paraná; geração hidrelétrica; democracy; participation; water resources management; coastline basin of Paraná; hydroelectric generation; CNPQ::CIENCIAS SOCIAIS APLICADAS